Effects of geometry of nano-structured materials on their thermal expansion: tellurium nanocylinders as model system. (1st June 2007) - Krstic, Vojislav; Rikken, Geert L.J.A.; Kaempgen, Martti; Roth, Siegmar; , Jon A. Beukes
The temperature-dependence of the atomic bond-lengths and -angles of the unit cell of crystalline tellurium nanocylinders (a few m in length and some 100 nm in diameter) have been investigated by X-ray diffraction in the range from 370 K to 100 K. With decrease in temperature, significant deviations from the established temperature-dependence of the bulk tellurium lattice parameters are observed. The observations in the temperature expansion are attributed to the nano-size and symmetry of the tellurium nanocylinders. The study demonstrates that a qualitative change in the material's properties is achieved when approaching the nano-scale. This opens the road for the possibility of deliberate tailoring of materials properties by proper choice of size and symmetry for thermo-mechanical applications.